Design and analysis of isolated high step-up Y-source DC/DC resonant converter for photovoltaic applications. Issue 1 (31st December 2023) - Sugali, Harinaik; Sathyan, Shelas
ABSTRACT: This paper presents the design and analysis of an isolated high step-up Y-source DC/DC converter for photovoltaic systems. At high switching frequencies, the conventional impedance source converter (ISC) experiences higher switching losses. To mitigate this, a high gain soft-switched frequency-modulated Y-source DC/DC converter is proposed. Here, soft switching is implemented on the Y-source impedance converter by creating quasi-resonance during a shoot-through instant. Thus, quasi-resonance occurs by an LC resonant tank, and it is formed using a resonant capacitor and leakage inductance of a transformer. It ensures that all the active switches are turned off with zero current switching (ZCS) and the voltage stress on each switch is much lower than the output voltage with lower turn-off voltage spikes. Thus, it eliminates the need for a snubber circuit. The output voltage is regulated by frequency modulation with the ON period of all four active switches kept constant. The converter can also deliver a continuous input current (CIC) and high voltage gain with a small shoot-through duty ratio ( d S T ) . The galvanic isolation of the converter helps to eliminate the leakage current issues and safety hazards faced by the non-isolated counterparts. The proposed topology has all the inherent characteristics of a typical impedance source DC/DC converter with higher conversion efficiency over a wide range of output loads. The proposed converter achieves 96.46% of full load efficiency. Finally, a 200W prototype is built and tested in the laboratory to verify the converter design and performance.